Telacebec: an investigational antibacterial for the treatment of tuberculosis (TB). (1st February 2022) - Lee, Bei Shi; Pethe, Kevin
ABSTRACT: Introduction: Tuberculosis is an infectious disease that affected more than 50 million people and killed 6.7 million patients in the past 5 years alone. Additionally, rising incidence of treatment resistance threatens the global effort to eradicate this disease. With limited options available, additional novel antibiotics are needed for the treatment of multidrug-resistant tuberculosis (MDR-TB). Telacebec is a first-in-class antibiotic that targets the pathogen's energy metabolism. Areas covered: This paper provides an overview of the recent progress in the development and testing of telacebec. We discuss published clinical data and examine the design and setup of its clinical trials. We also offer insights on the therapeutic potential of telacebec and aspects of which should be evaluated in the future. Expert opinion: The first phase 2a trial showed a correlation between dosage and bacterial load in patient sputum, which should be confirmed using a direct measurement method such as colony-forming unit counting. Its clinical efficacy, favorable pharmacokinetic properties, low arrhythmogenic risk, and activity against MDR-TB strains make telacebec a suitable candidate for further development. Future clinical testing in combination with approved second-line drugs will reveal its full potential against MDR-TB. Considering recent preclinical studies, we also recommend initiating clinical trials for Buruli ulcer and leprosy.